The Effect of Exercise Order on Maximum Strength Development in Resistance Trainings - Özbay, Serhat; Ulupınar, Süleyman; Çınar, Vedat; Akbulut, Taner (My University, 2019)
The aim of this study is to investigate the effect of exercise order on maximum strength development in resistance trainings.Thirty six male wrestlers (age = 21.6 ± 2.0 years; height = 169.8 ± 8.7 cm; body mass = 76.6 ± 11.1 kg) participated in the study.The participants performed two different resistance training programs for 12 weeks. First group (Gr1) performed the exercisesinvolving large muscle groups at initial. The other group (Gr2) performed the same exercises in the opposite order. For the Gr1,the exercise order was bench press (BP), lat pulldown (LPD), shoulder press (SP), biceps curl (BC), triceps extension (TE). Forthe Gr2, the exercise order was TE, BC, SP, LPD and BP. Before and after the 12-week training period, 1 repeat maximum (1RM)loads were measured in all exercises. According to the results, 1RM loads of all exercises increased significantly in both groups(5.8-16.7%). However, 1RM load increase in the BP and LPD exercises were significantly higher in Gr1 compared to Gr2. Nosignificant difference was found between the groups in 1RM load increase of SP, BC and TE exercises. As a result it isrecommended that exercises involving large muscle groups should be performed first.
Keywords: Sağlık Bilimleri ve Hizmetleri; Spor Bilimleri